Energy absorption of patterned thin-walled structures - Song, Jie. (2013)
Thin-walled tubular structures are widely used as energy absorbing devices. However, conventional tubes show an excessively high initial peak force when loaded axially and may fail in global bending, especially when subject to oblique loading with large load angle. In this thesis, tubes with patterns are considered. First, a new origami pattern has been proposed for square, hexagonal and octagonal tubes under axial loading, which can reduce the initial peak force and increase the energy absorption. Next, square tubes with a novel topological pattern under axial loading are studied. Experimental and numerical results show that this pattern can effectively reduce the initial peak force and increase the specific energy absorption. Finally, the topological pattern is used for square tubes subject to oblique impact. A new design method has been proposed which can effectively prevent the tubes from collapsing in global bending at large loading angle.